EVALUATION OF THE IN VITRO ANTI-INFLAMMATORY ACTIVITY OF THE ETHANOL EXTRACT FROM THE SEEDS OF ENTADA PURSAETHA DC - NARASIMHARAO BHOGIREDDY,; PARDHASARADHI MATHI,; VENUGOPAL GADDAGUTI,; NAGAVAMSIKRISHNA AMBATIPUDI,; VENKATA RAMAN BOKKA, (International Journal of Pharma and Bio Sciences, 2016)
Inflammation mainly depends upon the disease clinically defined as a pathophysiological process characterized by edema and pain. Inflammation occurs in response to injury, lipid peroxidation or infection. The signs and symptoms of inflammation include redness, swelling, heat, pain and loss of function of the affected area. Cyclooxygenase (COX1&2) are the key enzymes involves in the conversion of arachidonic acid to prostaglandins which are playing main role in inflammation. Entada pursaetha seed extract was prepared and it was explored for its phytochemical constituents, scavenging and anti-inflammatory activity. This article explores the medicinal values of the Entada pursaetha which is having strong anti-inflammatory and analgesic properties. Diclofenac standard and Entada pursaetha ethanolic seed extract both exhibited equal absorbance at 500 μg/mL in BSA assay.